Biodiversity among sheep and goat reared under different agroclimatic regions of West Bengal, India - PAL, ARUNA; CHATTERJEE, PARESH NATH; DAS, SHUVENDU; BATTOBYAL, SUBHASHIS; BISWAS, PURNENDU; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2017)
Biodiversity in West Bengal, India is enormous in terms of climate and living creatures, particularly animals. Livestock species as sheep and goat forms the main backbone for rural economy and reared basically for meat production. The objective of the present study was to characterize them and study the growth, biomorphometric traits, reproduction, wool characteristics, blood biochemical profile, and disease resistance traits and aimed to reveal the biodiversity existing within the goat and sheep breeds reared in different agroclimatic zones of the state. Phylogenetic tree constructed by multivariate cluster analysis with identified traits of eight different sheep breeds of eastern India revealed the emergence of Birbhum sheep as a genetically distinct sheep breed of dry arid region of India with greater percentage of rudimentary ear as its unique physical characteristic. Molecular characterization with mitochondrial gene as Cytochrome B gene confirmed genetic uniqueness of Birbhum sheep. Black Bengal (BB) goat was found to be the only goat breed distributed throughout the West Bengal.